Monetary Policy and MSME Credit in the Perspective of ECM - Nabila, Shofiya; Devia, Vietha (Contemporary Studies in Economic, Finance and Banking, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a strategic sector in the national economy, but the stability of their financing is influenced by macroeconomic conditions and monetary policy. Studies on the relationship between monetary policy and MSME credit financing are still relatively limited. This study aims to analyze the effect of the benchmark interest rate, money supply, and inflation on MSME credit financing. Using monthly data from 2014 to 2024 and the Error Correction Model (ECM) approach, this study examines the short-term and long-term relationships between variables. The results show that the benchmark interest rate does not have a significant impact in the short term but has a significant positive impact in the long term. The money supply has a significant positive impact in both the short and long term, while inflation has a significant negative impact on both time horizons. These findings provide empirical evidence of the effectiveness of monetary policy in influencing SME financing. The implications of the study emphasize that the formulation of monetary policy needs to consider the differences in short-term and long-term dynamics to better align with the sustainable financing needs of SMEs.